The disease of the Andes (Erythremic syndromes) - Monge M., Carlos (1928)
Report submitted to the Faculty of Medicine of Lima on physiological studies, pathophysiological and clinical undertaken in man of the Andean highlands, mainly in Oroya (12,200 feet) and Morococha (14,800 feet), 1927.